Unravelling Indonesia’s Foreign Aid Interest Towards Fiji From a Multi-Frame Perspective - Bintang Corvi Diphda; Andrew Elnathan; Fahdina Camela Farcha; Delvin Pramatya Arianto; Refa Defanda Witanto; Muhammad Rafi Anwar; Fabio Philbert Theodore (Universitas Darul Ulum, 2026)
Indonesian official discourse often presents this aid as development cooperation and South-South partnership. However, these narratives do not fully explain the political logic of the relationship. Using van der Veen’s seven-frame model of foreign aid, this study analyzes Indonesia’s aid to Fiji as a multi-frame foreign-policy instrument. The article adopts a qualitative single-case study design. It uses desk review as the main data collection method and analyzes official Indonesian documents, embassy performance reports, strategic plans, gray literature and academic studies through thematic analysis. The findings show that Indonesia’s aid to Fiji has evolved from episodic assistance into a more institutionalized package of grants, humanitarian relief, technical cooperation, scholarships, reconstruction support, health assistance and sectoral training. The analysis further shows that Indonesia’s aid is driven by overlapping humanitarian, security, influence, economic, reputational, enlightened self-interest and obligation-based motives. In particular, aid helps Indonesia strengthen its diplomatic position in the Pacific, build a positive image, expand regional access, and manage Papua-related political pressures. The article contributes to foreign aid and South-South Cooperation scholarship by showing that solidarity and strategic interest can operate together in Global South aid diplomacy. In the Indonesia-Fiji case, solidarity provides the normative language that legitimizes aid, while strategic interests shape its direction as an instrument of national interest.